The Use of Information Technology in Teaching Exact and Natural Sciences - Hamro Roziboyevich Mallayev (Genius Publishing Group, 2022)
This article reveals the purpose, content and essence of using information technologies and advanced innovative pedagogical technologies in the organization of the educational process in our Republic, as well as the role of education
Keywords: information technologies; innovative technologies; Internet; multimedia